2022
DOI: 10.1001/jamanetworkopen.2022.5557
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adjuvant Chemotherapy With Overall Survival Among Patients With Locally Advanced Gastric Cancer After Neoadjuvant Chemotherapy

Abstract: Key Points Question Is adjuvant chemotherapy associated with a survival benefit for patients with locally advanced gastric cancer who underwent curative-intent gastrectomy after neoadjuvant chemotherapy? Findings In this cohort study of 462 patients with locally advanced gastric cancer from Western and Eastern countries, adjuvant chemotherapy was associated with significantly improved survival in patients with a lymph node ratio of at least 9% compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…Since neoadjuvant chemotherapy plays an important role in treating advanced and resectable GC patients [ 42 , 43 ], we enrolled four common chemotherapeutic drugs to assess their responsiveness between low-risk and high-risk groups through the R package “pRRophetic”. The half-maximal inhibitory concentration (IC50) of each chemotherapeutic drug in all samples showed that the risk score is positively correlated with the concentration of each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Since neoadjuvant chemotherapy plays an important role in treating advanced and resectable GC patients [ 42 , 43 ], we enrolled four common chemotherapeutic drugs to assess their responsiveness between low-risk and high-risk groups through the R package “pRRophetic”. The half-maximal inhibitory concentration (IC50) of each chemotherapeutic drug in all samples showed that the risk score is positively correlated with the concentration of each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had several limitations. Being a retrospective study [ 19 , 20 ], the inherent bias (incidence-prevalence bias) cannot be excluded, and because it was a single institution, hospital-based study, generalization to the entire population would be difficult. Although the five-year survival is a standard method of representation, due to a lack of available data, we have only presented two-year survival.…”
Section: Discussionmentioning
confidence: 99%
“…The need for adjuvant therapy, especially in patients who achieve a pCR, has been widely debated. Retrospective studies in China and USA reported that patients who received adjuvant therapy after neoadjuvant treatment could gain survival benefits, especially when the lymph node ratio was above 9% and in patients who completed at least four cycles of adjuvant chemotherapy [ 44 45 ]. However, contradictions were observed in patients who achieved a pCR.…”
Section: Impacts Of Nac In Clinical Practicementioning
confidence: 99%
“…Mokdad et al [ 45 ] reported that adjuvant therapy showed favored results in even patients with ypT0 (HR, 0.63; 95% CI, 0.41–0.97) or ypN0 (HR, 0.68; 95% CI, 0.54–0.87). However, data from China did not show the survival benefit of adjuvant therapy in ypT0-1 (HR, 0.52; 95% CI, 0.04–7.07) or ypN0 (HR, 0.79; 95% CI, 0.38–1.65) subgroups [ 44 ]. It is difficult to draw conclusions based on current data; and other factors, especially the management of adverse effect and patients’ intention to undergo chemotherapy, should be considered.…”
Section: Impacts Of Nac In Clinical Practicementioning
confidence: 99%